PREVALENCE OF VITREOUS CORTEX REMNANTS IN EYES WITH PRIMARY RHEGMATOGENOUS RETINAL DETACHMENT UNDERGOING VITRECTOMY. Issue 7 (July 2021) - Assi, Alexandre; Khoueir, Ziad
Abstract : Background/Purpose: To evaluate the prevalence and extent of vitreous cortex remnants (VCR) on the surface of the retina in eyes with primary rhegmatogenous retinal detachment (RRD) and posterior vitreous detachment. Methods: Triamcinolone acetonide was injected in the vitreous cavity of 100 consecutive cases of acute primary RRD undergoing pars plana vitrectomy. A multivariate regression analysis was performed to determine any association between the presence and pattern of stained VCR on the surface of the retina and the following variables: age, diabetes, axial length, phakic status, extent of RRD, and macular status. Results: Vitreous cortex remnants were found in 42 eyes. These were focal in eight eyes and diffuse in 34 eyes. Age was the only strong and independent risk factor associated with the presence of VCR ( P = 0.0019). Age ( P < 0.0001), axial length ( P = 0.0037), and phakia ( P = 0.01) were independent risk factors associated with the diffuse pattern. Neither diabetes, extent of RRD, nor macular status were significant risk factors for the presence or extent of VCR. Conclusion: Older patients with primary RRD and posterior vitreous detachment seem to be at a higher risk of having diffuse VCR. Further studies are needed to investigate the relevance of VCR in the pathogenesis, progression and treatment of RD. Abstract : Vitreous cortex remnants were found in 42% of eyes undergoing vitrectomy for primary rhegmatogenous retinal detachment associated with a posterior vitreous detachment. Older age seems to be a strong and independent risk factor associated with the presence of vitreous cortex remnants.